Identification of a new epitope for HIV‐neutralizing antibodies in the gp41 membrane proximal external region by an Env‐tailored phage display library. Issue 2 (27th December 2012) - Zhou, Mingkui; Meyer, Torsten; Koch, Stefanie; Koch, Joachim; von Briesen, Hagen; Benito, José M.; Soriano, Vincent; Haberl, Annette; Bickel, Markus; Dübel, Stefan; Hust, Michael; Dietrich, Ursula
<x xml:space="preserve">Abstract</x> HIV controllers are a valuable source for the identification of HIV‐neutralizing antibodies, as chronic infection over decades allows extensive affinity maturation of antibodies for improved Ag recognition. We analyzed a small cohort of elite controllers (ECs) for HIV‐neutralizing antibodies using a panel of standardized HIV‐1 pseudovirions on TZM‐bl cells. An HIV‐1 Env‐tailored phage display library was generated to select epitopes targeted by neutralizing antibodies in the EC26 plasma sample showing the broadest neutralizing activity. Selected Env fragments were mostly allocated to the membrane proximal external region of gp41. After preabsorbing the EC26 plasma with the selected phage EC26‐2A4, we achieved 50% depletion of its neutralizing activity. Furthermore, antibodies affinity‐purified with the EC26‐2A4 epitope from EC26 plasma showed neutralizing activity, proving that the selected phage indeed contains an epitope targeted by neutralizing plasma antibodies. Epitope fine mapping of the purified plasma antibodies on peptide arrays identified a new epitope overlapping, but clearly distinct, from the prominent 2F5 epitope. Of note, the purified antibodies did not show autoreactivity with cardiolipin, whereas low reactivity with phosphatidylserine comparable to mAb 2F5 was observed. Thus, this new epitope represents a promising candidate for further analysis in view of HIV vaccine development.